High-dispersion small-size PtCo intermetallic compound oxygen reduction reaction electrocatalyst and preparation method thereof
By in situ conversion on the carbon matrix to form a high-dispersion small-size PtCo intermetallic compound electrocatalyst, the problem of poor stability of Pt-based alloy electrocatalyst and difficulty in preparing uniform dispersion catalysts is solved, and efficient catalytic performance of oxygen reduction reaction and high power density and stability of fuel cells are achieved.
Patent Information
- Application Number
- CN202311269022.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-03-28
AI Technical Summary
The existing Pt-based alloy electrocatalysts have poor stability under harsh working conditions and are difficult to achieve the preparation of a uniformly dispersed small-size Pt-M intermetallic catalyst, which affects the development and commercialization of fuel cells.
A high-dispersion small-size PtCo intermetallic compound oxygen reduction electrocatalyst was developed, and a carbon-supported PtCo intermetallic compound electrocatalyst was transformed into a carbon-supported PtCo intermetallic compound electrocatalyst by in situ on the activated carbon matrix, and a wet chemical method was used to mix and heat activation reduction technology.
High catalytic activity and durability are achieved, the ORR catalytic performance in acidic media is better than that of commercial Pt/C, the oxygen reduction half-wave potential can reach 0.91V, the taffel slope is small, and it shows high power density and good stability in fuel cell tests.
Smart Images

Figure CN119725582A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inorganic nanomaterials, and specifically relates to a highly dispersed small-sized PtCo intermetallic compound oxygen reduction reaction electrocatalyst and a preparation method thereof. Background Art
[0002] Proton exchange membrane fuel cells (PEMFCs) have attracted increasing attention in the field of global sustainable energy due to their unique technological advantages of high energy density and low environmental impact. However, the slow kinetics of the cathode oxygen reduction reaction (ORR) and the poor stability of traditional platinum (Pt)-based electrocatalysts have seriously restricted the development and commercialization of PEMFCs. Introducing transition metal (M=Fe, Co, Ni, etc.) elements into Pt to form alloys is an effective strategy to improve the reaction kinetics and reduce the amount of Pt by introducing strain and adjusting the electronic structure of Pt. However, under the harsh working conditions of PEMFCs, Pt-based alloy catalysts will deactivate rapidly due to the rapid leaching of transition metals. In chemically ordered intermetallic compounds, Pt and transition metal atoms are assigned to specific positions, which can effectively improve the activity and durability of Pt-based alloy electrocatalysts. Compared with disordered alloys, the enhanced stability of Pt-based intermetallic compounds can be attributed to the close arrangement of Pt and M atoms, which achieves stronger dd orbital coupling. In addition, when the atomic radius of M is smaller than that of Pt, the Pt-rich layer is subjected to strong lattice compressive strain, which can relieve the excessive adsorption of oxygen-containing intermediates on Pt surface sites, thereby improving its catalytic activity. Therefore, controlling the strain conditions is of great significance for improving Pt-based alloy catalysts. However, achieving homogeneous Pt-M intermetallic catalysts with an ideal particle size (5 nm or less) remains challenging.
[0003] In recent years, a lot of research has been done on the migration and agglomeration of Pt-based nanoparticles under high temperature conditions, such as coating disordered nanoparticles with oxides or polymers, protective matrix-assisted annealing, and confined co-reduction. Although these methods can produce Pt-based metal particles with ideal size and uniform distribution, their preparation methods are too complicated to achieve reliable batch preparation, and also increase the cost of synthesis and use. In addition, they are not conducive to the construction of the three-phase interface and inevitably affect the mass transport during the ORR process. Therefore, designing Pt-based metal intermetallic oxygen reduction catalysts that can fully expose active sites while maintaining their own stability is of great significance for the commercial application of proton exchange membrane fuel cells. Summary of the invention
[0004] In order to solve the balance problem between stability and activity of carbon-supported Pt-based alloy electrocatalysts, the present invention has developed a highly dispersed small-sized PtCo intermetallic compound oxygen reduction reaction electrocatalyst and its preparation method. The preparation process of this new catalyst is simple and easy, and it has excellent performance. It is expected to be used as a cathode ORR catalyst layer material to replace commercial Pt / C, thereby greatly reducing the commercial cost of hydrogen fuel cells. It has the potential value of large-scale market application and can effectively promote the rapid development of the new energy economy.
[0005] In the first aspect, the present invention provides a highly dispersed small-sized PtCo intermetallic compound oxygen reduction reaction electrocatalyst. The highly dispersed small-sized PtCo intermetallic compound oxygen reduction reaction electrocatalyst is a carbon-supported PtCo intermetallic oxygen reduction reaction electrocatalyst, comprising a carbon matrix and core-shell structured nanoparticles supported on the surface of the carbon matrix; the core-shell structured nanoparticles comprise a highly ordered PtCo intermetallic compound as an inner core and a Pt-rich layer coated on the surface of the PtCo intermetallic compound as an outer shell; the mass percentage of the metal in the oxygen reduction reaction electrocatalyst is 5 to 25%, preferably 15 to 20%; wherein the mass ratio of Pt to Co is 1 to 5:1.
[0006] The enhanced stability of the PtCo intermetallic compound in the electrocatalyst of the present invention can be attributed to the close arrangement of Pt and Co atoms, thereby achieving stronger dd orbital coupling. The presence of the Pt layer on the surface of the PtCo intermetallic compound nanoparticles (alloy nanoparticles) further enhances the stability of the Pt-based intermetallic compound. More importantly, the Pt layer will produce a strong lattice compression strain, thereby alleviating the excessive adsorption of oxygen-containing intermediates on the surface Pt sites and improving the catalyst activity. However, excessive compression strain will make the catalyst adsorb too weakly on the intermediates, which is not conducive to the activation of the reactant (O2).
[0007] Preferably, the order degree of the PtCo intermetallic compound is 80% to 95%.
[0008] Preferably, the average size of the core-shell nanoparticles is ≤5 nm, preferably 2 to 5 nm. Uniformly dispersed small-sized core-shell nanoparticles are conducive to the establishment of a three-phase interface, thereby exposing more catalytic active sites and enhancing mass transport during the ORR process.
[0009] Preferably, the specific surface area of the electrocatalyst is 200 to 600 g / m 2 .
[0010] The electrocatalyst of the present invention has high catalytic activity and durability. In an acidic medium, under the same loading condition, it has better ORR catalytic performance than commercial Pt / C, and its oxygen reduction half-wave potential (E 1 / 2) can reach 0.91V, and has a small Tafel slope (53.2mV dec -1 In the H2 / O2 fuel cell test, the material was used as a cathode catalyst (with a loading of 0.1 mg Pt cm -2 ) Its maximum power density can reach 2.21W cm -1 ; Under H2 / air conditions, its maximum power density can reach 1.13W cm -1 , and also has good operating stability, with no performance degradation during the 50h discharge process.
[0011] In the second aspect, the present invention provides a method for preparing a highly dispersed small-sized PtCo intermetallic compound oxygen reduction reaction electrocatalyst as described in any of the above items. A carbon-supported PtCo intermetallic compound oxygen reduction reaction electrocatalyst is formed by in-situ conversion of precious metal Pt and transition metal Co on an activated carbon matrix; preferably, the preparation method comprises: activating the carbon matrix; dispersing the activated carbon matrix and the metal complex of Pt and the metal complex of Co in an organic solvent, mixing them evenly and then drying to obtain a bimetallic carbon composite material; heat treating the bimetallic carbon composite material in a reducing atmosphere to obtain a highly dispersed small-sized PtCo intermetallic compound oxygen reduction reaction electrocatalyst.
[0012] Preferably, the carbon matrix is carbon black.
[0013] Preferably, the activation temperature is 100-600° C., and the activation time is 1-6 hours.
[0014] Preferably, the metal complex of Pt is at least one of a metal Pt phthalocyanine complex, a metal Pt porphyrin complex, and a metal Pt acetylacetonate; the metal complex of Co is at least one of a metal Co phthalocyanine complex, a metal Co porphyrin complex, and a metal Co acetylacetonate.
[0015] Preferably, the mass ratio of the Pt metal complex, the Co metal complex and the activated carbon matrix is (0.1-2.5):(0.5-5.5):(1-25).
[0016] Preferably, the organic solvent is at least one of methanol, ethanol, isopropanol, dimethyl sulfoxide, ether, chloroform and acetone.
[0017] Preferably, the heat treatment temperature is 500-1100° C., the heat treatment time is 2-8 hours, and the reducing atmosphere is a mixture of H 2 / Ar.
[0018] The preparation method of the present invention is simple and easy to operate, and can omit the complicated post-processing process, and can prevent the agglomeration of metal particles during the carbonization process, and is suitable for the preparation of catalyst materials including precious metals and transition metals. The oxygen reduction reaction electrocatalyst formed by the preparation method is mainly composed of carbon-supported metal particles, and the activity and durability of the Pt-based alloy electrocatalyst are improved by forming chemically ordered intermetallic compounds. The uniformly dispersed small-sized nanoparticles are conducive to the production of a higher electrochemical active area and a fast material transfer pathway. Through the synergistic catalysis between the two metals, it exhibits higher ORR catalytic activity and durability than commercial Pt / C in an acidic medium, greatly reducing the application cost of the cathode Pt-based catalyst, and having a higher economic benefit. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The TEM (transmission electron microscope) image of the L10-PtCo / C material prepared in Example 1 of the present invention is shown; Figure 2 shows the particle size distribution diagram of the L10-PtCo / C material prepared in Example 1 of the present invention; Figure 3 The HAADF-STEM (high angle annular dark field scanning transmission electron microscope) image of the L10-PtCo / C material prepared in Example 1 of the present invention is shown; Figure 4 shows the XRD pattern of the L10-PtCo / C material prepared in Example 1 of the present invention; Figure 5 A comparison diagram of linear scanning polarization curves of the L10-PtCo / C material prepared in Example 1 of the present invention and commercial Pt / C in an acidic medium is shown; Figure 6 A comparison diagram of the Tafel slopes of the L10-PtCo / C material prepared in Example 1 of the present invention and commercial Pt / C in an acidic medium is shown; Figure 7 The power density curve of the L10-PtCo / C material prepared in Example 1 of the present invention in the H2 / O2 fuel cell test system is shown; the performance of the catalyst in the H2 / O2 fuel cell test system is shown, and the two curves are respectively the UI curve and the PI curve; Figure 8 The power density curve of the L10-PtCo / C material prepared in Example 1 of the present invention in the H2 / air fuel cell test system is shown; the performance of the catalyst in the H2 / O2 fuel cell test system is shown, and the two curves are respectively the UI curve and the PI curve; Fig. 9The stability curve of the L10-PtCo / C material prepared in Example 1 of the present invention in a H2 / air fuel cell test system is shown; Fig.10 A comparison diagram of linear scanning polarization curves of the L10-PtCo / C material prepared in Example 1 of the present invention and the L10-PtCo / C-D1 material prepared in Comparative Example 1 in an acidic medium is shown; Fig.11 A comparison diagram of linear scanning polarization curves of the L10-PtCo / C material prepared in Example 1 of the present invention and the L10-PtCo / C-D2 material prepared in Comparative Example 2 in an acidic medium is shown; Fig.12 The TEM comparison diagram of the L10-PtCo / C-D3 material prepared in Comparative Example 3 of the present invention is shown; Fig.13 A comparison diagram of linear scanning polarization curves of the L10-PtCo / C material prepared in Example 1 of the present invention and the L10-PtCo / C-D3 material prepared in Comparative Example 3 in an acidic medium is shown; Fig.14 The TEM comparison diagram of the PtCo / C material prepared in Comparative Example 4 of the present invention is shown; Fig.15 A comparison diagram of linear scanning polarization curves of the L10-PtCo / C material prepared in Example 1 of the present invention and the PtCo / C material prepared in Comparative Example 4 in an acidic medium is shown. DETAILED DESCRIPTION
[0020] The present invention is further described by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention. Unless otherwise specified, each percentage refers to the percentage by mass. The highly dispersed small-sized PtCo intermetallic compound oxygen reduction reaction electrocatalyst and its preparation method described in the present invention are described below.
[0021] The current controllable synthesis of carbon-supported high-density and uniformly dispersed small-sized Pt-based intermetallic compound nanoparticles as cheap, efficient and durable cathode ORR electrocatalysts still faces great challenges. The present invention is a carbon-supported PtCo intermetallic compound oxygen reduction reaction electrocatalyst formed by in-situ conversion of precious metal Pt and transition metal Co on an activated carbon substrate.
[0022] Specifically, the present invention utilizes wet chemical high-energy mixing and thermal activation reduction, uses activated carbon materials such as carbon black as a carbon matrix, and simultaneously loads Pt and Co metal atoms onto the carbon matrix through high-energy mixing technology, and utilizes a thermal reduction process to ultimately form a uniformly dispersed intermetallic electrocatalyst with small-sized core-shell structured nanoparticles. The wet chemical high-energy mixing and thermal activation reduction process of the electrocatalyst improves the current complex preparation process of Pt-based catalysts and can achieve batch preparation of catalyst materials. The preparation method of the present invention provides a new strategy for synthesizing highly dispersed small-sized Pt-based intermetallic compound oxygen reduction catalysts, which improves the randomness of the formation process.
[0023] As an example, carbon black is used as a building block, and a Pt-based intermetallic compound catalyst with high dispersion and small size is finally formed through a wet chemical high-energy mixing technology and a thermal reduction process. Specifically, the following steps are included.
[0024] The carbon matrix (also referred to as the carbon substrate) is activated by potassium hydroxide under a reducing atmosphere. The carbon matrix can be activated by a thermal reduction process using an atmosphere furnace. For example, a mixture of a certain amount of carbon matrix and potassium hydroxide is placed in a tubular atmosphere furnace and treated under a reducing atmosphere. Subsequently, the activated (pre-)treated carbon matrix can be obtained by washing with water, filtering (taking filter cakes), and drying. Potassium hydroxide can corrode the carbon matrix to produce more oxygen-containing functional groups on its surface, which is conducive to efficient coordination with the metal in the next reaction. In some technical schemes, the mass ratio of the carbon matrix to potassium hydroxide is (0.2-0.8):1. Different from using hydroxide as a molten salt to separate metal ions and prevent agglomeration, the role of potassium hydroxide in the present invention is to mix with the carbon matrix to activate the carbon matrix. The reducing atmosphere can be a H2 / Ar mixed atmosphere. Among them, the volume ratio of H2 and Ar can be 5-10:90-95.
[0025] In the embodiment, carbon black is used as the carbon matrix. Carbon black is a kind of amorphous carbon, light, loose and extremely fine black powder. It is the product obtained by incomplete combustion or thermal decomposition of carbon-containing materials such as coal, natural gas, heavy oil, fuel oil, etc. under the condition of insufficient air. It has a large specific surface area and is therefore often used as a carrier material for loading metal nanoparticles. Carbon black includes but is not limited to at least one of XC-72, XC-72R, EC 300J, EC 600DJ, and BP-2000. The activation temperature and activation time can be optimized according to actual conditions. For example, the activation temperature can be 100-600°C (preferably 100-500°C), and the activation time is 1-6h.
[0026] The metal complex of Pt, the metal complex of Co and the activated carbon matrix are uniformly mixed, and a bimetallic carbon composite material (also referred to as a bimetallic carbon nanocomposite material) is obtained by a wet chemical method high-energy mixing technique. For example, the activated carbon matrix and the metal complex of Pt and the metal complex of Co are ultrasonically dispersed into an organic solvent, mixed uniformly and then dried to form a bimetallic carbon composite material. High-energy mixing is preferably used. For example, a high-energy mixer is used for mixing.
[0027] The metal complex is formed by metal ions and ligands through coordination chemical bonds. The ligands will play a good protective role on the central metal ions, reduce their surface energy, and prevent the metal ions from agglomerating and sintering during the heat treatment process, so that uniform dispersion can be achieved while producing smaller metal nanoparticles, which is a special advantage that metal nitrates do not have. The metal complex of Pt includes but is not limited to at least one of metal Pt phthalocyanine complexes, metal Pt porphyrin complexes, and metal Pt acetylacetonate. The metal complex of Co includes but is not limited to at least one of metal Co phthalocyanine complexes, metal Co porphyrin complexes, and metal Co acetylacetonate. The organic solvent includes but is not limited to at least one of methanol, ethanol, isopropanol, dimethyl sulfoxide, ether, chloroform, and acetone. In some technical solutions, the mass ratio of the metal complex of Pt, the metal complex of Co, and the activated carbon black is (0.1-2.5): (0.5-5.5): (1-25).
[0028] In one example, a certain amount of platinum phthalocyanine and cobalt porphyrin are added to a certain concentration of carbon black in methanol dispersion, subjected to high energy ultrasonic treatment for 30 minutes, and dried to obtain a Pt / Co bimetallic carbon composite material. The mass ratio of platinum phthalocyanine: cobalt porphyrin: activated carbon black can be (0.1-2.5): (0.5-5.5): (1-25).
[0029] The bimetallic carbon composite material is heat treated (pyrolyzed) in a H2 / Ar mixed atmosphere. In this process, the oxygen-containing functional groups in the carbon matrix can inhibit the migration and agglomeration of metal atoms at high temperatures, prevent the aggregation of metal atoms during the heat treatment process, and finally obtain a uniformly dispersed high-density small-sized PtCo carbon electrocatalyst. The volume ratio of H2 and Ar in the H2 / Ar mixed atmosphere can be 5-10:90-95.
[0030] The heat treatment can be carried out in a tube furnace. For example, after introducing H2 / Ar mixed gas into the tube furnace for 30 to 60 minutes, the mixture is heated to the heat treatment temperature at a heating rate of 5 to 10°C / minute. The heat treatment temperature can be 500 to 1100°C and the time can be 2 to 8 hours.
[0031] In one example, for example, a Pt / Co bimetallic carbon composite material can be spread flat on a magnetic boat, placed in a tubular furnace, and pyrolyzed at high temperature in a H2 / Ar mixed gas atmosphere, heated to 1000°C at a heating rate of 5°C / min and kept warm for 4 hours to obtain a highly dispersed small-sized PtCo intermetallic compound oxygen reduction reaction electrocatalyst.
[0032] The prior art uses a complex preparation process, including the selection of tungsten hexacarbonyl as a capping agent and the use of two different reducing agents in the process of preparing the core-shell structure. In contrast, the preparation strategy of the present invention is relatively simple, without the addition of a capping agent and without a two-step reduction process. From the perspective of material characterization, the particle size prepared by the present invention is about 5nm and the distribution density is relatively high. From the perspective of catalytic performance, the highly dispersed small-sized PtCo intermetallic compound oxygen reduction reaction electrocatalyst obtained by the present invention has an E of 1.000 for ORR. 1 / 2 It can reach 0.91 V (vs. RHE), indicating that its performance is much better than that of PtCo@PtIr.
[0033] The highly dispersed small-sized PtCo intermetallic compound oxygen reduction reaction electrocatalyst obtained by the preparation method of the present invention is a carbon-supported PtCo intermetallic compound oxygen reduction reaction electrocatalyst, comprising a carbon matrix and core-shell structured nanoparticles supported on the surface of the carbon matrix; the core-shell structured nanoparticles comprise a highly ordered PtCo intermetallic compound as an inner core and a Pt-rich layer coated on the surface of the PtCo intermetallic compound as an outer shell. Figure 3 As shown, the housing is spaced The Pt-
[111] surface, and the inner core is the spacing This further proves the existence of the core-shell structured nanoparticles of the present invention.
[0034] Core-shell nanoparticles refer to PtCo intermetallic compounds coated with a Pt shell on the outside, so they are considered to be intermetallic compound nanoparticles with a core-shell structure. The
[111] crystal plane of the outer Pt shell is considered to be the main active surface, and it also has very good stability. The form of the internal PtCo intermetallic compound will produce a strain regulation on the outer Pt shell, thereby promoting the overall ORR catalytic performance. At the same time, from the perspective of the formation process, the instability of Co makes it easy to lose, so it is bound to leave a Pt shell on the outer layer, thus forming this Pt shell-PtCo core core-shell structure.
[0035] The mass ratio of Pt to Co in the carbon-supported PtCo intermetallic oxygen reduction reaction catalyst is 1 to 5: 1, preferably 2: 1. This contributes to the presence of a Pt-rich layer on the surface of the intermetallic nanoparticles, further enhancing the activity and stability of the Pt-based intermetallic oxygen reduction reaction catalyst.
[0036] Preferably, the mass percentage of Pt and Co in the carbon-supported PtCo metal oxygen reduction reaction catalyst is 5-25%, preferably 15-20%. The increase in metal loading is due to the improvement of the preparation process. The high-energy mixing method adopted in the present invention is conducive to the formation of metal (M)-O bonds on the carbon matrix, which can prevent the loss of metals, thereby converting more metal ions into the form of metal compounds, so that the metal loading is increased. In this type of catalyst, metals serve as the main active sites, and their higher content is conducive to the improvement of catalytic performance. In particular, the mass ratio of the two metals Pt and Co is preferably 2: 1, which is conducive to the formation of a core-shell structure (outer: Pt shell, inner: PtCo metal compound) rich in Pt layer.
[0037] The electrocatalyst has high-density uniformly dispersed core-shell structure nanoparticles; the particle size is ≤5nm. The electrocatalyst has uniformly dispersed small-size nanoparticles (≤5nm), which greatly improves the utilization rate of active sites and has ultra-high hydrogen-oxygen fuel cell output power and good discharge stability.
[0038] The electrocatalyst of the present invention has high-density dispersed metal nanoparticles and an ordered intermetallic compound structure. Preferably, the order of the PtCo intermetallic compound can reach 80% to 95%. The ordering degree is determined by the ratio of the (110) peak area to the combined area of the (111), (200), and (002) peaks, expressed as S(110) / (S(111)+S(200)+S(002)). This ratio is used as a quantitative measure of the order because it is directly linearly related to the order. The stable arrangement of the bimetal in the electrocatalyst improves the durability of the catalyst in an acidic environment. Moreover, the electrocatalyst utilizes the synergistic catalytic effect between the bimetallics, which is beneficial to improve the ORR catalytic performance of the Pt-based metal catalyst in an acidic medium, thereby producing ultra-high proton exchange membrane fuel cell output power and good discharge stability.
[0039] The PtCo intermetallic compound oxygen reduction reaction electrocatalyst will adjust the d-band center of Pt through compressive strain, thereby affecting the adsorption performance of the catalyst to the reactant. The present invention introduces PtCo intermetallic compounds to synergistically promote electron transfer from Co sites to Pt, thereby reducing the strong adsorption of Pt to the reaction species and improving the intrinsic catalytic activity of the material; at the same time, the close arrangement of Pt and Co atoms is utilized to achieve stronger dd orbital coupling and improve its catalytic stability. The specific reason is that due to the differences in electronic structure and coordination environment between different metals, directional electron transfer will occur between heterogeneous metals, thereby generating corresponding electron-rich and electron-deficient centers; among which unequal amounts and different types of heteroatoms doping are the main reasons for inducing electron transfer. Moreover, the electrocatalyst has a suitable size (average size ≤5nm), which effectively improves the stability under battery discharge conditions. Importantly, the uniformly dispersed small-sized nanoparticles can ensure that the active sites are fully exposed, thereby quickly transporting oxygen during the ORR process, thereby improving the original catalytic performance of the Pt-based catalyst.
[0040] The PtCo intermetallic compound oxygen reduction reaction electrocatalyst of the present invention has a half-wave potential, Tafel slope and limiting current density that are superior to those of commercial Pt / C in 0.1M HClO4 solution. At the same time, in H2 / O2 and H2 / air fuel cell tests, it has a peak power density higher than that of Pt / C and better battery stability. Moreover, the preparation method of the bimetallic compound oxygen reduction reaction electrocatalyst is simple and easy to operate, and a cathode electrode material equivalent to commercial Pt / C is achieved with a lower noble metal loading, which is of great significance for promoting the large-scale commercialization of hydrogen fuel cells.
[0041] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples in a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values exemplified below.
[0042] Example 1
[0043] First, a pre-activated carbon substrate was prepared using carbon black. Taking XC-72 as an example, 5g of carbon black and 10g of potassium hydroxide were ground and placed in a tube furnace. After passing H2 / Ar mixed gas with a volume ratio of 5:95 for 10 minutes, it was heated to 500°C at a heating rate of 5°C / min and kept warm for 4 hours. The activated carbon black (ACs) was then washed with water, filtered and dried. Subsequently, the activated carbon black was evenly dispersed in a methanol solution with a mass ratio of 20:1:5 with platinum phthalocyanine and cobalt porphyrin. After ultrasonic treatment for 30 minutes, it was loaded into a high-energy mixer, centrifuged and dried after running for 5 hours to obtain a bimetallic carbon composite material. The bimetallic carbon composite material was placed in a tubular furnace, and a H2 / Ar mixed gas with a volume ratio of H2 to Ar of 5:95 was introduced for 30 minutes, then heated to 1000°C at a heating rate of 5°C / min and kept warm for 3 hours to obtain a carbon-loaded PtCo intermetallic compound electrocatalyst (L10-PtCo / C).
[0044] like Figure 1 and Figure 2 As shown, in the PtCo intermetallic compound electrocatalyst, the particle size of the core-shell structured nanoparticles is about 2-5 nm, and the particles are uniformly dispersed.
[0045] like Figure 3 and 4 As shown, the catalyst has a core-shell nanostructure with Pt as the outer shell and PtCo intermetallic compound as the inner core.
[0046] The carbon-supported PtCo intermetallic compound electrocatalyst prepared in Example 1 was tested for its electrocatalytic oxygen reduction reaction performance: using Shanghai Chenhua 760E electrochemical workstation and American PINE rotating disk electrode, Ag / AgCl electrode and carbon rod were used as reference electrode and counter electrode respectively, and 0.1M HClO4 solution was used as electrolyte. The working electrode was polished with Al2O3 powder, and then the electrode was ultrasonically cleaned with deionized water and ethanol respectively. Dry under infrared lamp, take 5mg of the above-prepared L10-PtCo / C material and add it to a mixture of 30μL Nafion and 1.25mL ethanol for ultrasonic treatment to obtain a uniformly dispersed suspension. 10μL of the suspension was added dropwise to the polished glassy carbon electrode, and the solvent was evaporated and removed under infrared lamp irradiation to obtain a working electrode with a L10-PtCo / C electrocatalyst film coated on the surface of the glassy carbon electrode. Before the test, high-purity nitrogen or oxygen was introduced for 15 minutes to saturate the gas in the electrolyte, and scanning activation was performed at a speed of 50mV / s at room temperature.
[0047] The oxygen reduction performance of the L10-PtCo / C material prepared in Example 1 was tested. Figure 5 As shown, the half-wave potential (E 1 / 2) is 0.91V, which is better than the commercial Pt / C catalyst tested under the same conditions (E 1 / 2 =0.89V). At the same time, it also has a better Tafel slope than Pt / C catalyst ( Figure 6 In the H2 / O2 fuel cell test, L10-PtCo / C catalyst (loading: 0.1 mg Pt cm -2 The peak power density can reach (2.21W cm -2 )( Figure 7 ). Under H2 / air conditions, its maximum power density can reach 1.13W cm -1 ( Figure 8 ), and also has good operating stability, with no performance degradation during the 50h discharge process ( Fig. 9 ). Thus, the material of Example 1 exhibits excellent electrocatalytic ORR performance in both an O2-saturated 0.1M HClO4 solution and an actual hydrogen fuel cell test system.
[0048] Example 2
[0049] 5g of carbon black (XC-72R) and 10g of potassium hydroxide were ground and placed in a tube furnace. After passing H2 / Ar mixed gas with a volume ratio of H2 to Ar of 5:95 for 10 minutes, the mixture was heated to 500℃ at a heating rate of 5℃ / min and kept warm for 4 hours. The activated carbon black (ACs) was then uniformly dispersed in a methanol solution with a mass ratio of 20:1:5 with platinum phthalocyanine and cobalt porphyrin. After ultrasonic treatment for 30 minutes, the mixture was placed in a high-energy mixer, centrifuged and dried after running for 5 hours to obtain a bimetallic carbon composite material. The bimetallic carbon composite material was placed in a tube furnace, passed H2 / Ar mixed gas with a volume ratio of H2 to Ar of 5:95 for 30 minutes, heated to 1000℃ at a heating rate of 5℃ / min and kept warm for 3 hours to obtain a carbon-supported PtCo intermetallic compound electrocatalyst (L10-PtCo / C). The material exhibits excellent electrocatalytic oxygen reduction reaction performance in an O2-saturated 0.1M HClO4 solution.
[0050] Example 3
[0051] 5g of carbon black (BP-2000) and 10g of potassium hydroxide were ground and placed in a tube furnace. After passing H2 / Ar mixed gas with a volume ratio of H2 to Ar of 5:95 for 10 minutes, the mixture was heated to 500℃ at a heating rate of 5℃ / min and kept warm for 4 hours. The activated carbon black (ACs) was then uniformly dispersed in a methanol solution with a mass ratio of 20:1:5 with platinum phthalocyanine and cobalt porphyrin. After ultrasonic treatment for 30 minutes, the mixture was placed in a high-energy mixer, centrifuged and dried after running for 5 hours to obtain a bimetallic carbon composite material. The bimetallic carbon composite material was placed in a tube furnace, passed H2 / Ar mixed gas with a volume ratio of H2 to Ar of 5:95 for 30 minutes, heated to 1000℃ at a heating rate of 5℃ / min and kept warm for 3 hours to obtain a carbon-supported PtCo intermetallic compound electrocatalyst (L10-PtCo / C). The material exhibits excellent electrocatalytic oxygen reduction reaction performance in an O2-saturated 0.1M HClO4 solution.
[0052] Example 4
[0053] 5g of carbon black (XC-72R) and 15g of potassium hydroxide were ground and placed in a tube furnace. After passing H2 / Ar mixed gas with a volume ratio of H2 to Ar of 5:95 for 10 minutes, the mixture was heated to 200℃ at a heating rate of 5℃ / min and kept warm for 4 hours. The activated carbon black (ACs) was then uniformly dispersed in a methanol solution with a mass ratio of 20:1:5 with platinum phthalocyanine and cobalt porphyrin. After ultrasonic treatment for 30 minutes, the mixture was placed in a high-energy mixer, centrifuged and dried after running for 5 hours to obtain a bimetallic carbon composite material. The bimetallic carbon composite material was placed in a tube furnace, passed H2 / Ar mixed gas with a volume ratio of H2 to Ar of 5:95 for 30 minutes, heated to 1000℃ at a heating rate of 5℃ / min and kept warm for 3 hours to obtain a carbon-supported PtCo intermetallic compound electrocatalyst (L10-PtCo / C). The material exhibits excellent electrocatalytic oxygen reduction reaction performance in an O2-saturated 0.1M HClO4 solution.
[0054] Example 5
[0055] 5g of carbon black (XC-72R) and 10g of potassium hydroxide were ground and placed in a tube furnace. After passing H2 / Ar mixed gas with a volume ratio of H2 to Ar of 5:95 for 10 minutes, the mixture was heated to 500℃ at a heating rate of 5℃ / min and kept warm for 6 hours. The activated carbon black (ACs) was then washed with water, filtered and dried to obtain the activated carbon black. Subsequently, the activated carbon black was uniformly dispersed in a methanol solution with a mass ratio of 20:1:5 with platinum phthalocyanine and cobalt porphyrin. After ultrasonic treatment for 30 minutes, the mixture was placed in a high-energy mixer, centrifuged and dried after running for 5 hours to obtain a bimetallic carbon composite material. The bimetallic carbon composite material was placed in a tube furnace, and after passing H2 / Ar mixed gas with a volume ratio of H2 to Ar of 5:95 for 30 minutes, the mixture was heated to 1000℃ at a heating rate of 5℃ / min and kept warm for 3 hours to obtain a carbon-supported PtCo intermetallic compound electrocatalyst (L10-PtCo / C). The material exhibits excellent electrocatalytic oxygen reduction reaction performance in an O2-saturated 0.1M HClO4 solution.
[0056] Example 6
[0057] 5g of carbon black (XC-72R) and 10g of potassium hydroxide were ground and placed in a tube furnace. After passing H2 / Ar mixed gas with a volume ratio of H2 to Ar of 5:95 for 10 minutes, the mixture was heated to 500℃ at a heating rate of 5℃ / min and kept warm for 4 hours. The activated carbon black (ACs) was then uniformly dispersed in a dimethyl sulfoxide solution with platinum phthalocyanine and cobalt porphyrin at a mass ratio of 20:1:5. After ultrasonic treatment for 30 minutes, the mixture was placed in a high-energy mixer, centrifuged and dried after running for 5 hours to obtain a bimetallic carbon composite material. The bimetallic carbon composite material was placed in a tube furnace, passed H2 / Ar mixed gas with a volume ratio of H2 to Ar of 5:95 for 30 minutes, heated to 1000℃ at a heating rate of 5℃ / min and kept warm for 3 hours to obtain a carbon-supported PtCo intermetallic compound electrocatalyst (L10-PtCo / C). The material exhibited excellent electrocatalytic oxygen reduction reaction performance in an O2-saturated 0.1M HClO4 solution.
[0058] Example 7
[0059] 5g of carbon black (XC-72R) and 20g of potassium hydroxide were ground and placed in a tube furnace. After passing H2 / Ar mixed gas with a volume ratio of H2 to Ar of 5:95 for 10 minutes, the mixture was heated to 500℃ at a heating rate of 5℃ / min and kept warm for 4 hours. The activated carbon black (ACs) was then uniformly dispersed in a dimethyl sulfoxide solution with platinum phthalocyanine and cobalt phthalocyanine at a mass ratio of 20:1:5, ultrasonically treated for 30 minutes, loaded into a high-energy mixer, centrifuged and dried after running for 5 hours to obtain a bimetallic carbon composite material. The bimetallic carbon composite material was placed in a tube furnace, passed H2 / Ar mixed gas with a volume ratio of H2 to Ar of 5:95 for 30 minutes, heated to 1000℃ at a heating rate of 5℃ / min and kept warm for 3 hours to obtain a carbon-supported PtCo intermetallic compound electrocatalyst (L10-PtCo / C). The material exhibited excellent electrocatalytic oxygen reduction reaction performance in an O2-saturated 0.1M HClO4 solution.
[0060] Example 8
[0061] 5g of carbon black (XC-72R) and 10g of potassium hydroxide were ground and placed in a tube furnace. After passing H2 / Ar mixed gas with a volume ratio of H2 to Ar of 5:95 for 10 minutes, the mixture was heated to 500℃ at a heating rate of 5℃ / min and kept warm for 4 hours. The activated carbon black (ACs) was then uniformly dispersed in a methanol solution with a mass ratio of 10:1:5 with platinum phthalocyanine and cobalt porphyrin. After ultrasonic treatment for 30 minutes, the mixture was placed in a high-energy mixer, centrifuged and dried after running for 5 hours to obtain a bimetallic carbon composite material. The bimetallic carbon composite material was placed in a tube furnace, and after passing H2 / Ar mixed gas with a volume ratio of H2 to Ar of 5:95 for 30 minutes, the mixture was heated to 1000℃ at a heating rate of 5℃ / min and kept warm for 3 hours to obtain a carbon-supported PtCo intermetallic compound electrocatalyst (L10-PtCo / C). The material exhibits excellent electrocatalytic oxygen reduction reaction performance in an O2-saturated 0.1M HClO4 solution.
[0062] Example 9
[0063] 5g of carbon black (XC-72R) and 10g of potassium hydroxide were ground and placed in a tube furnace. After passing H2 / Ar mixed gas with a volume ratio of H2 to Ar of 5:95 for 10 minutes, the mixture was heated to 500℃ at a heating rate of 5℃ / min and kept warm for 4 hours. The activated carbon black (ACs) was then uniformly dispersed in a methanol solution with a mass ratio of 20:2:5 with platinum phthalocyanine and cobalt porphyrin. After ultrasonic treatment for 30 minutes, the mixture was placed in a high-energy mixer, centrifuged and dried after running for 5 hours to obtain a bimetallic carbon composite material. The bimetallic carbon composite material was placed in a tube furnace, passed H2 / Ar mixed gas with a volume ratio of H2 to Ar of 5:95 for 30 minutes, heated to 1000℃ at a heating rate of 5℃ / min and kept warm for 3 hours to obtain a carbon-supported PtCo intermetallic compound electrocatalyst (L10-PtCo / C). The material exhibits excellent electrocatalytic oxygen reduction reaction performance in an O2-saturated 0.1M HClO4 solution.
[0064] Example 10
[0065] 5g of carbon black (XC-72R) and 10g of potassium hydroxide were ground and placed in a tube furnace. After passing H2 / Ar mixed gas with a volume ratio of H2 to Ar of 5:95 for 10 minutes, the mixture was heated to 500℃ at a heating rate of 5℃ / min and kept warm for 4 hours. The activated carbon black (ACs) was then uniformly dispersed in a methanol solution with a mass ratio of 20:1:8 with platinum phthalocyanine and cobalt porphyrin. After ultrasonic treatment for 30 minutes, the mixture was placed in a high-energy mixer, centrifuged and dried after running for 5 hours to obtain a bimetallic carbon composite material. The bimetallic carbon composite material was placed in a tube furnace, passed H2 / Ar mixed gas with a volume ratio of H2 to Ar of 5:95 for 30 minutes, heated to 1000℃ at a heating rate of 5℃ / min and kept warm for 3 hours to obtain a carbon-supported PtCo intermetallic compound electrocatalyst (L10-PtCo / C). The material exhibits excellent electrocatalytic oxygen reduction reaction performance in an O2-saturated 0.1M HClO4 solution.
[0066] Embodiment 11
[0067] 5g of carbon black (XC-72R) and 10g of potassium hydroxide were ground and placed in a tube furnace. After passing H2 / Ar mixed gas with a volume ratio of H2 to Ar of 5:95 for 10 minutes, the mixture was heated to 500℃ at a heating rate of 5℃ / min and kept warm for 4 hours. The activated carbon black (ACs) was then uniformly dispersed in a methanol solution with a mass ratio of 20:1:5 with platinum phthalocyanine and cobalt porphyrin. After ultrasonic treatment for 30 minutes, the mixture was placed in a high-energy mixer, centrifuged and dried after running for 5 hours to obtain a bimetallic carbon composite material. The bimetallic carbon composite material was placed in a tube furnace, and after passing H2 / Ar mixed gas with a volume ratio of H2 to Ar of 5:95 for 30 minutes, the mixture was heated to 800℃ at a heating rate of 5℃ / min and kept warm for 3 hours to obtain a carbon-supported PtCo intermetallic compound electrocatalyst (L10-PtCo / C). The material exhibits excellent electrocatalytic oxygen reduction reaction performance in an O2-saturated 0.1M HClO4 solution.
[0068] Example 12
[0069] 5g of carbon black (XC-72R) and 15g of potassium hydroxide were ground and placed in a tube furnace. After passing H2 / Ar mixed gas for 10 minutes, the mixture was heated to 500℃ at a heating rate of 5℃ / min and kept warm for 4 hours. The activated carbon black (ACs) was then washed with water, filtered and dried to obtain the activated carbon black. Subsequently, the activated carbon black, platinum phthalocyanine and cobalt porphyrin were uniformly dispersed in a methanol solution at a mass ratio of 20:1:5, ultrasonically treated for 30 minutes, loaded into a high-energy mixer, centrifuged and dried after running for 5 hours to obtain a bimetallic carbon composite material. The bimetallic carbon composite material was placed in a tube furnace, and after passing H2 / Ar mixed gas with a volume ratio of H2 to Ar of 5:95 for 30 minutes, the mixture was heated to 1000℃ at a heating rate of 5℃ / min and kept warm for 6 hours to obtain a carbon-supported PtCo intermetallic compound electrocatalyst (L10-PtCo / C). The material exhibited excellent electrocatalytic oxygen reduction reaction performance in an O2-saturated 0.1M HClO4 solution.
[0070] Comparative Example 1
[0071] 5g of carbon black (XC-72) and 10g of potassium hydroxide were ground and placed in a tube furnace. After passing H2 / Ar mixed gas with a volume ratio of H2 to Ar of 5:95 for 10 minutes, the mixture was heated to 500℃ at a heating rate of 5℃ / min and kept warm for 4 hours. The activated carbon black (ACs) was then washed with water, filtered and dried to obtain the activated carbon black. Subsequently, the activated carbon black and platinum phthalocyanine were uniformly dispersed in a methanol solution at a mass ratio of 20:1, ultrasonically treated for 30 minutes, loaded into a high-energy mixer, centrifuged and dried after running for 5 hours to obtain a single metal carbon composite material. The single metal carbon composite material was placed in a tube furnace, passed H2 / Ar mixed gas with a volume ratio of H2 to Ar of 5:95 for 30 minutes, heated to 1000℃ at a heating rate of 5℃ / min and kept warm for 3 hours to obtain a carbon-supported Pt metal nanoparticle catalyst (A-Pt / C). The material exhibited poor oxygen reduction electrocatalytic performance in an O2-saturated 0.1M HClO4 solution ( Fig.10 The main reason is the lack of the synergistic catalytic effect of the bimetallic species, which makes the Pt site have a strong adsorption energy of intermediate oxygen species and is not easy to desorb, resulting in lower oxygen reduction catalytic activity.
[0072] Comparative Example 2
[0073] 5g of carbon black (XC-72) and 10g of potassium hydroxide were ground and put into a tube furnace. After the H2 / Ar mixed gas with a volume ratio of H2 to Ar of 5:95 was introduced for 10 minutes, it was heated to 500℃ at a heating rate of 5℃ / min and kept warm for 4 hours, washed with water, filtered and dried to obtain activated carbon black (ACs). Subsequently, the activated carbon black, platinum phthalocyanine and cobalt porphyrin were uniformly dispersed in a methanol solution at a mass ratio of 20:1:5, ultrasonically treated for 30 minutes, centrifuged and dried to obtain a bimetallic carbon composite material. The mixed bimetallic carbon composite material was placed in a tube furnace, and after the H2 / Ar mixed gas with a volume ratio of H2 to Ar of 5:95 was introduced for 30 minutes, it was heated to 1000℃ at a heating rate of 5℃ / min and kept warm for 3 hours to obtain a carbon-supported PtCo intermetallic compound electrocatalyst (L10-PtCo / C-D2). The material exhibited poor oxygen reduction electrocatalytic performance in an O2-saturated 0.1M HClO4 solution ( Fig.11 ). The main reason is that the metal species and carbon are not fully mixed using a high-energy mixing device, which causes the metal atoms to aggregate and agglomerate during the pyrolysis process, thereby reducing the active site density of the catalyst and making its oxygen reduction catalytic activity low.
[0074] Comparative Example 3
[0075] 5g of carbon black (XC-72) was directly dispersed in a methanol solution with platinum phthalocyanine and cobalt porphyrin in a mass ratio of 20:1:5. After ultrasonic treatment for 30 minutes, the mixture was centrifuged and dried to obtain a bimetallic carbon composite material. The uniformly mixed bimetallic carbon composite material was placed in a tubular furnace, and a H2 / Ar mixed gas with a volume ratio of H2 and Ar of 5:95 was introduced for 30 minutes. Then, the mixture was heated to 1000°C at a heating rate of 5°C / min and kept warm for 3 hours to obtain a carbon-supported PtCo intermetallic compound electrocatalyst (L10-PtCo / C-D3). This material has a large particle size ( Fig.12 The material exhibited poor oxygen reduction electrocatalytic performance in an O2-saturated 0.1M HClO4 solution compared to PtCo intermetallic compound catalysts (e.g. L10-PtCo / C). Fig.13 The main reason is that the unactivated carbon lacks more exposed oxygen-containing functional groups, which is not conducive to the bonding of MO species, making it difficult to limit the migration of metal atoms on the carbon matrix, resulting in the agglomeration of metal atoms and the reduction of the active site density of the catalyst, resulting in low oxygen reduction catalytic activity.
[0076] Comparative Example 4
[0077] 5g of carbon black (XC-72) and 10g of potassium hydroxide were ground and placed in a tubular furnace. After passing H2 / Ar mixed gas with a volume ratio of H2 and Ar of 5:95 for 10 minutes, the mixture was heated to 500℃ at a heating rate of 5℃ / min and kept warm for 4 hours. The activated carbon black (ACs) was then washed with water, filtered and dried to obtain the activated carbon black. Subsequently, the activated carbon black and platinum phthalocyanine were uniformly dispersed in a methanol solution at a mass ratio of 20:1:5. After ultrasonic treatment for 30 minutes, the mixture was placed in a high-energy mixer, centrifuged and dried after running for 5 hours to obtain a bimetallic carbon composite material. The bimetallic carbon composite material was placed in a tubular furnace, and after passing H2 / Ar mixed gas with a volume ratio of H2 and Ar of 5:95 for 30 minutes, the mixture was heated to 400℃ at a heating rate of 5℃ / min and kept warm for 3 hours to obtain a carbon-supported PtCo alloy catalyst (PtCo / C) ( Fig.14 The material exhibited poor oxygen reduction electrocatalytic performance in an O2-saturated 0.1M HClO4 solution compared to PtCo intermetallic compound catalysts (e.g. L10-PtCo / C). Fig.15 ). The main reason is that the lower heat treatment temperature causes the Pt-Co bimetallic to exist in the form of an alloy instead of forming an intermetallic compound.
Claims
1. A highly dispersed small-sized PtCo intermetallic compound oxygen reduction reaction electrocatalyst, characterized in that: The highly dispersed small-sized PtCo intermetallic compound oxygen reduction reaction electrocatalyst is a carbon-supported PtCo intermetallic oxygen reduction reaction electrocatalyst, comprising a carbon matrix and core-shell structured nanoparticles supported on the surface of the carbon matrix; the core-shell structured nanoparticles comprise a highly ordered PtCo intermetallic compound as an inner core and a Pt-rich layer coated on the surface of the PtCo intermetallic compound as an outer shell; the mass percentage of the metal in the oxygen reduction reaction electrocatalyst is 5 to 25%, preferably 15 to 20%; wherein the mass ratio of Pt to Co is 1 to 5:
1.
2. The oxygen reduction reaction electrocatalyst according to claim 1, characterized in that The order degree of the PtCo intermetallic compound is 80% to 95%.
3. The oxygen reduction reaction electrocatalyst according to claim 1 or 2, characterized in that: The average size of the core-shell structured nanoparticles is ≤5 nm, preferably 2 to 5 nm.
4. The oxygen reduction reaction electrocatalyst according to any one of claims 1 to 3, characterized in that The specific surface area of the oxygen reduction reaction electrocatalyst is 200 to 600 g / m 2 .
5. The method for preparing a highly dispersed small-sized PtCo intermetallic compound oxygen reduction reaction electrocatalyst according to any one of claims 1 to 4, characterized in that: A carbon-supported PtCo intermetallic compound oxygen reduction reaction electrocatalyst is formed by in-situ conversion of precious metal Pt and transition metal Co on an activated carbon matrix; preferably, the preparation method comprises: activating the carbon matrix; dispersing the activated carbon matrix and the metal complex of Pt and the metal complex of Co in an organic solvent, mixing them evenly and then drying to obtain a bimetallic carbon composite material; heat-treating the bimetallic carbon composite material in a reducing atmosphere to obtain a highly dispersed small-sized PtCo intermetallic compound oxygen reduction reaction electrocatalyst.
6. The preparation method according to claim 5, characterized in that: The carbon matrix is carbon black.
7. The preparation method according to claim 5 or 6, characterized in that: The activation temperature is 100-600°C, and the activation time is 1-6h.
8. The preparation method according to any one of claims 5 to 7, characterized in that: The metal complex of Pt is at least one of a metal Pt phthalocyanine complex, a metal Pt porphyrin complex, and a metal Pt acetylacetonate; the metal complex of Co is at least one of a metal Co phthalocyanine complex, a metal Co porphyrin complex, and a metal Co acetylacetonate.
9. The preparation method according to any one of claims 5 to 8, characterized in that: The mass ratio of the Pt metal complex, the Co metal complex and the activated carbon matrix is (0.1 to 2.5): (0.5 to 5.5): (1 to 25).
10. The preparation method according to any one of claims 5 to 9, characterized in that: The organic solvent is at least one of methanol, ethanol, isopropanol, dimethyl sulfoxide, ether, chloroform and acetone.
11. The preparation method according to any one of claims 5 to 10, characterized in that: The heat treatment temperature is 500-1100° C., the heat treatment time is 2-8 hours, and the reducing atmosphere is a mixed gas of H2 / Ar.
Citation Information
Cited By
Method for preparing Pt-based oxygen reduction catalyst based on metalloporphyrin polymer
CN122246160A